Analysis of Ovarian Artery Doppler - Additional Parameter for Diagnosis of Polycystic Ovary in Bangladeshi Female of Reproductive Age Group (Bangladesh Journal of Radiology and Imaging, 2026)
Background: Polycystic ovarian syndrome is a common and complex metabolic, endocrine & reproductive disorder of females of reproductive age. Objective: The aim of the present study was to evaluate the inherent changes in vascular flow pattern of ovarian artery in patients with endocrinologically and clinically confirmed polycystic ovaries in comparison with normal females of reproductive age having spontaneous ovulatory cycles. Method: Total 100 females of reproductive age (18-40 years) were included in this study, 50 of which have been diagnosed as polycystic ovarian syndrome (PCOS) and the other 50 as a control group, without any evidence of PCOS. Transvaginal Ultrasonography (TVS) was performed to evaluate ovarian morphology & Doppler indices (RI & PI) of ovarian arteries. Results: Ovarian artery Doppler indices were deranged in women with polycystic ovaries .The mean values of PI is 4.08+0.36 and RI 0.97+0.09.The mean age of the patients was 26.4+5.3 years and 86% of the patients were obese. Conclusion: Despite the complexity of the pathophysiological interactions & the heterogeneity of the anatomical & clinical presentations of polycystic ovarian syndrome, the assessment of ovarian morphology & Doppler indices by TVS provide the pathological status & the degree of progression of the disease. The result of the present study demonstrated the more significant vascular changes rather than low significant morphological changes. Hence it is possible to include this criteria as an additional marker to diagnose PCOS, which aids early therapeutic intervention, delaying the progression of the syndrome. It will also help in evaluation of the post therapeutic status of PCOS and in taking decision of extending the duration of therapy.BJRI, 2024; VOL. 32(2): 124-129